In vivo molecular imaging of HER2 expression in a rat model of Barrett's esophagus adenocarcinoma. Issue 4 (7th April 2014) - Realdon, S.; Dassie, E.; Fassan, M.; Dall'Olmo, L.; Hatem, G.; Buda, A.; Arcidiacono, D.; Diamantis, G.; Zhang, H.; Greene, M. I.; Sturniolo, G. C.; Rugge, M.; et al.
Summary Human epidermal growth factor receptor 2 (HER2) is involved in the malignant progression of several human cancers, including esophageal adenocarcinoma (EAC). The purpose of this study was to evaluate HER2 overexpression and to explore the feasibility of confocal laser endomicroscopy for in vivo molecular imaging of HER2 status in an animal model of Barrett's‐related EAC. Rats underwent esophagojejunostomy with gastric preservation. At 30 weeks post‐surgery, the esophagus of 46 rats was studied; endoscopic and histological findings were correlated with HER2 immunofluorescence on excised biopsies and gross specimens. At this age, 23/46 rats developed Barrett's esophagus (BE), and 6/46 had cancer (four EAC and two squamous cell carcinomas). A significant overexpression of HER2 was observed in esophageal adenocarcinoma compared with normal squamous esophagus (9.4‐fold) and BE (6.0‐fold). AKT and its phosphorylated form were also overexpressed in cancer areas. Molecular imaging was performed at 80 weeks post‐surgery in four rats after tail injection of fluorescent‐labeled anti‐HER2 antibody. At this age, 3/4 rats developed advance adenocarcinoma and showed in vivo overexpression of HER2 by molecular confocal laser endomicroscopy with heterogeneous distribution within cancer; no HER2 signal was observed in normal or Barrett's tissues. Therefore, HER2 overexpression is a typical feature of the surgical induced model of EAC that can be easily quantified in vivo using an innovative mini‐invasive approach including confocal endomicroscopy; this approach may avoid limits of histological evaluation of HER2 status on 'blinded' biopsies.